Surgical versus Conservative Management of Granular Myringitis: A single-centre Randomized Control Trial (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Treatment of granular myringitis (GM) is diverse with no definitive management.Objective: The aim of the present study was to see the effectiveness of different interventions for treating granular myringitis.Methodology: This was a single centred, parallel, randomized control trial. This study was done at the Specialized ENT Hospital of SAHIC, Dhaka from July 2010 to June 2012. Patients presenting with granular myringitis of 18 years of age or more with both sexes were included. All patients were divided into two groups by simple random sampling method of which patients of group A were treated by surgical treatment and that of group B were treated by medical treatment. Medical treatment was given in the form of topical ear drops and surgical treatment was performed by surgical debridement of granulation tissue followed by chemical cauterization. Repeated follow up was performed up to 6 months in both groups of treated patients. The primary outcome was the resolution of granulation tissue. During follow-up the secondary outcome variables were recurrence, perforation of the TM and any other complications or complain from the patients.Results: A total number of 60 patients were studied of which 30 patients were treated medically and 30 patients were treated surgically. The cure rate was higher in surgical treatment (80%) than conservative (16.7%) (p=0.011). The recurrence rate (17.24%) is also less in surgical group compared to medical treatment group (77.27%) (p=0.001).Conclusion: Surgical treatment is a more successful treatment modality for granular myringitis.Journal of National Institute of Neurosciences Bangladesh, 2019;5(1): 64-68